The Busieness Cycle and the Level of Bank Loans to Enterprises - Mikołajczak, Paweł (Studia Oeconomica Posnaniensia, 2015)
Because of the importance of revenue and gross domestic product as factors determining the demand by companies for bank loans, this study presents the results of an analysis of the impact of the level of turnover and gross domestic product on changes in the level of bank loans during the period between the fi rst quarter of 2006 and the fourth quarter of 2013. Th e study also analyses the correlation between the level of total revenue for economic entities, GDP and the dynamics of changes regarding company bank loans.